The Legitimation of Religion in Profit Seeking: The Role of National Shari‘āh Division of The Indonesian Muslim Council (DSN-MUI) - Izmuddin, Iiz; Amalia, Euis; Nasir, Mohamad Abdun; Muttaqin, Farid (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Religious legitimacy is a potent means of achieving one's objectives, including the pursuit of economic benefits. This is how Islamic financial institutions employ the fatwa of the National Sharia Council (DSN-MUI) in their operations. Nonetheless, this objective is often in conflict with the noblest religious ideals of justice, equality, and humanity. This paper aims to explain how the DSN-MUI fatwa acquires religious legitimacy, as well as the repercussions of granting this legitimacy to the public that utilizes Islamic financial institutions. The collected data consists of the texts of DSN-MUI fatwa from 2000 to 2021 as well as the results of interviews with DSN-MUI practitioners of Islamic economics, and pertinent academicians. The data is then descriptively and critically analyzed. The findings of the study suggest that there are three fatwa issued by the DSN-MUI that legitimize profits gained by Islamic financial institutions. However, this method may violate significant religious norms. This paper also concludes that competition between conventional and Islamic financial institutions is a significant factor in the emergence of this legitimacy.